2010
DOI: 10.1186/1743-422x-7-130
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prognostic biomarkers for Interferon-based therapy to Hepatitis C Virus patients: a metaanalysis of the NS5A protein in subtypes 1a, 1b, and 3a

Abstract: BackgroundHepatitis C virus (HCV) is a worldwide health problem with no vaccine and the only approved therapy is Interferon-based plus Ribavarin. Response prediction to treatment has health and economic impacts, and is a multi-factorial problem including both host and viral factors (e.g: age, sex, ethnicity, pre-treatment viral load, and dynamics of the HCV non-structural protein NS5A quasispecies). We implement a novel approach for extracting features including informative markers from mutations in the non-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…However, amino acid substitutions in the core-coding regions of different genotypes appear to be related to insulin, oxidative stress, or steatosis resistance, variable responses in IFN-␣/ribavirin combination therapy, and hepatocellular carcinoma (HCC) (427). Core amino acid 70 and 91 polymorphisms have recently been used to predict IFN-␣ treatment response; for example, Q/H70 and M91 in patients with genotype 1b predict a slow or no response to IFN-␣, whereas patients infected with HCV harboring R70 and L91 are more likely to obtain a rapid sustained response (246,453,722).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…However, amino acid substitutions in the core-coding regions of different genotypes appear to be related to insulin, oxidative stress, or steatosis resistance, variable responses in IFN-␣/ribavirin combination therapy, and hepatocellular carcinoma (HCC) (427). Core amino acid 70 and 91 polymorphisms have recently been used to predict IFN-␣ treatment response; for example, Q/H70 and M91 in patients with genotype 1b predict a slow or no response to IFN-␣, whereas patients infected with HCV harboring R70 and L91 are more likely to obtain a rapid sustained response (246,453,722).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Another group suggested that IRRDR was unlikely to be an independent factor affecting the outcome of PEG-IFN plus RBV therapy [43]. Substitution of aa 2356 in HCV G1b and 2368 in HCV G1a were noted as markers of prognosis in IFN-based therapy on meta-analysis [44]. In contrast, aa substitution at particular positions within IRRDR was reported not to affect the outcome of PEG-IFN plus RBV therapy [41].…”
Section: Interferon Ribavirin Resistance-determining Region (Irrdr) Amentioning
confidence: 99%
“…During the last decade bioinformatics approaches have been used to predict different aspects of viruses [7][8][9][10]. Recently these methods even have been used to predict highrisk types of human papillomaviruses (HPVs) which is the *Address correspondence to this author at the Department of Biotechnology, Faculty of Advanced Sciences and Technologies, University of Isfahan, Isfahan, Iran; Tel: +98311-7934391; Fax: +98311-7932342; E-mail: h.mohabatkar@ast.ui.ac.ir etiological agents in nearly all cases of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%